Increased serum sialic acid in diabetic retinopathy of type 1 diabetes - YAVUZ, DİLEK; ÇERMAN, EREN; ÇELİKER ATABERK, HANDE; ERASLAN, MUHSİN; ŞAHİN, ÖZLEM (My University, 2013)
AIM: To investigate the potential association between serum sialic acid and diabetic retinopathy and its several grades. METHODS: We studied the level of serum sialic acid in 70 patients. Thirty control vs 40 type 1 diabetics and with different levels of diabetic retinopathy as well. RESULTS: We found higher levels of serum sialic acid level in diabetics compared to control subjects (95.95±9.5 vs 45.05±19.91 mmoL/L, P=0.0001). We also observed a progressive rise in its concentration as the level of diabetic retinopathy increased (P<0.05) but the correlation was weak. Serum sialic acid level correlated positively with blood glucose level (r=0.67, P=0.0001). CONCLUSION: Increase in serum sialic acid levels seems to be related to the stage of the retinopathy and may help us to determine the extent of retinopathy in type 1 diabetic patients. But we think that we need more detailed studies to get a more precise conclusion.
Keywords: Diabetes; Diabetic retinopathy; HbA1c; Serum; Sialic acid